A sectorial fuzzy consensus algorithm for the formation flight of multiple quadrotor unmanned aerial vehicles. (November 2020) - Ollervides-Vazquez, E Javier; Rojo-Rodriguez, Erik G; Garcia-Salazar, Octavio; Amezquita-Brooks, Luis; Castillo, Pedro; Santibañez, Victor
This paper presents an algorithm based on fuzzy theory for the formation flight of the multi-quadrotors. For this purpose, the mathematical model of N -quadrotor unmanned aerial vehicles is presented using the Newton-Euler formulation. The strategy of the formation flight is based on a structure composed by a sectorial fuzzy controller and the linear systems whose state variables are the position and velocity of the i th quadrotor. The stability analysis is described as a generalized form for N -quadrotor unmanned aerial vehicles and it is based on the Lyapunov theory. This analysis demonstrates that the closed-loop system is globally asymptotically stable so that the quadrotors unmanned aerial vehicles reach the consensus. Numerical simulation demonstrates the robustness of the proposed scheme for the formation flight even in the presence of disturbances. Finally, experimental results show the feasibility of the proposed algorithm for the formation flight of multiple unmanned aerial vehicles.